2001
DOI: 10.1088/0953-4075/34/19/307
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of the Auger cascade following 3d→5p photoexcitation in Kr

Abstract: Resonant Auger transitions from the 3d −1 5p photoexcited states in Kr to the 4s −1 4p −1 5p and 4s −2 5p levels and subsequent Auger decay to the 4p 4 and 4s4p 5 states of Kr 2+ are studied by means of angle-resolved electron spectroscopy. The angular anisotropy parameters β are determined for most of the prominent lines in the spectrum of emitted electrons. It is found that the first-step spectator transitions are strongly anisotropic, while the secondstep participator transitions are almost isotropic. Exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 35 publications
(49 reference statements)
4
51
1
Order By: Relevance
“…Because the X-ray transitions accompanying the cascade decay of inner-shell vacancies are less probable than the Auger transitions, the cascade affected emission spectra are less investigated, the results are mainly obtained for inert gases [27,33,[80][81][82][83][84] as well as for Fe [37], Ag [80], and Pb, Th, U [85]. During the last years some angle resolved studies of the Auger cascades following photoexcitation from an inner shell were performed for Ar, Kr, and Xe [31,[86][87][88][89].…”
Section: Introductionmentioning
confidence: 99%
“…Because the X-ray transitions accompanying the cascade decay of inner-shell vacancies are less probable than the Auger transitions, the cascade affected emission spectra are less investigated, the results are mainly obtained for inert gases [27,33,[80][81][82][83][84] as well as for Fe [37], Ag [80], and Pb, Th, U [85]. During the last years some angle resolved studies of the Auger cascades following photoexcitation from an inner shell were performed for Ar, Kr, and Xe [31,[86][87][88][89].…”
Section: Introductionmentioning
confidence: 99%
“…A series of experimental and theoretical investigations have been carried out on the angular distribution spectra of resonantly excited noble gases [16][17][18][19]21]. From the comparison with observed spectra, our computations clearly demonstrated that the angular dependence of the electron emission can be understood only-if the level structure and splitting is treated properly.…”
Section: Angular Distribution and Coherence Transfer In The Auger Spementioning
confidence: 88%
“…For a 3d ! 5p excitation in krypton, moreover, both the excitation and de-excitation process take place coherently through a number of levels and must be described in terms of a densitymatrix approach, in order to derive the angular distribution of the emitted electrons [19]. ItÕs likely that this effect is also important in the case of the 3d…”
Section: Angular Distribution and Coherence Transfer In The Auger Spementioning
confidence: 99%
“…However, less attention has been paid to the influence of overlapping resonances upon the atomic fluorescence, in contrast to the autoionization of inner-shell excited atoms [17][18][19]. Only rather recently, we explored the angular and polarization properties of the emitted photons in the two-step radiative cascade 1s2p…”
Section: Introductionmentioning
confidence: 99%